444 Readability, accessibility, quality, visual design and content of online information on dementia medication: a quantitative evaluation. (13th April 2023) - Rea, R; Parsons, C
Abstract: Introduction: Information on health conditions, encompassing information about treatment, is abundant on the Internet (1). Little is known about the standard of online information available in relation to dementia medications. Aim: To evaluate current information online on dementia medications, in terms of readability, information quality, accessibility, and content quality. Methods: Websites were identified by searching Google using the terms 'dementia medicines' and 'dementia medication'. Searches were conducted using a private browser setting to reduce the influence of previous searches on websites returned. The top 20 websites returned using each term were included. Readability was assessed using the Simple Measure of Gobbledygook (SMOG) instrument (<10 = good, 10-12 = adequate, >12 = poor). Quality of information was assessed using the 16-item DISCERN instrument (for each item >4=good, 3-4 = adequate and <3 = poor), and accessibility determined using the AChecker tool. Understandability and actionability were measured using the Patient Education Materials Assessment Tool (PEMAT; >80% = good, 70-80% = adequate and <70% = poor). Content was assessed using an 11-item content assessment tool (> 4=good, 3-4 = adequate, <3 = poor) (2). One researcher (RR) identified and evaluated the websites, and a second researcher (CP) independently evaluated a random sample (10%) of these websites for validation. Results: Due to overlap between the top 20 websites using the two search terms, 24 websites in total were evaluated. SMOG scores ranged from 11.4 to 20.7 for 'dementia medications' (mean 14.4) and from 11.6 to 20.8 (mean 14.6) for 'dementia medicines'. Websites with good or adequate quality information ranged from 95.8% (n=23) for the DISCERN item 'Is it clear that there may be more than one treatment choice?' to 16.7% (n=4) for the item 'Does it describe what would happen if no treatment is used?'. The AChecker tool identified a mean number of 14.8 and 13.9 accessibility issues per website for 'dementia medications' and 'dementia medicines' respectively; most commonly relating to misuse of font and lack of headers. PEMAT scores ranged from 66% (n=16) to 93% (n=22) for understandability and from 17% to 83% for actionability. Content quality varied from 29% (n=7) of websites covering 'How long it takes for medication to produce results', 'Uncommon side effects of medication' and 'Effects of stopping medication' to 95.8% (n=23) of websites covering 'Choice of medication' and 'Advantages of medication' in good to adequate detail. Conclusion: Overall, readability of websites providing information about dementia medications was poor, and quality of information varied. Many websites performed well in understandability, but not actionability. Adequacy of detail in content varied. Website development and refinement is needed to improve readability, accessibility, actionability and information and content quality relating to dementia medications. This study provides the first evaluation of websites providing information on dementia medications based on the domains of readability, accessibility and information and content quality. Limitations are: the websites evaluated do not fully represent the range of health information available online, exclusion of user-generated content and social media platforms, and inclusion of English language websites only. References: 1. Wiegers TA, Hendriks M, Malanda U, de Boer D. Users' experiences with web-based health care information: qualitative study about diabetes and dementia information presented on a governmental website. J Med Internet Res 2019;21(7):e11340 2. Hall B, Howard K, McCaffery K. Do cervical cancer screening patient information leaflets meet the HPV information needs of women? Patient Educ Couns 2008 72(1):78-87